Application of management matrix models for strategic planning of enterprise activities - Semenchuk Tetiana,; Vasiliha Sergii, (Technium Social Sciences Journal, 2020)
The importance of strategic planning enterprise activity is substantiated in the article. Detailed analysis of the management classic matrix models strategic planning, namely the Boston Consulting Group (BCG) method, the McKinsey method, and the Arthur D. Little method. Allowed to form a system basic models of strategic analysis. Which, unlike the existing ones, is built on the systematization of well-known matrix models of “packet management” in terms of tools, level of universalism and level of application. The article proposes an advanced strategic planning process for an enterprise with the application and combination of different types, methods, matrices and models, which includes three consecutive stages of analysis and planning. The authors of the article have also formulated and summarized the characteristics of matrices that are widely used in life and, above all, in the analysis of management activities. These are the change-resistance matrix and the Control Grid. The authors prove the importance and relevance of applying matrix methods in conjunction with the Blue Ocean strategy. The main instrument of the Blue Ocean Strategy is the Strategic Canvas - to diagnose and build such a strategy. In order to build an "outline strategy" for a company, it is necessary to identify the key characteristics of the products - theirs and their competitors. Analyzing a "strategic outline" allows the company to determine how well its market strategy is similar to that of its competitors. The creation of the "blue oceans" not only contributes to the strong growth and increase profits of enterprises, this strategic step has a serious positive effect on the consolidation of the existing brand the company in creating customers.